Study on synthesis of PANi/coir material for adsorption of DDT in contaminated soil extracts - Hop, Nguyen Quang; Que, Le Xuan (Vietnam Journal of Chemistry, 2017)
The efficiency of synthesized polyaniline (PANi) with the presence of coir in sulfuric acid medium and ammonium persulfate as oxidizing agent varies from 83.20 to 92.00 %. The obtained polyaniline/coir material was used for adsorption of dichloro diphenyl trichloroethane (DDT) - a pesticide which has been used and still causing serious pollution problems. The adsorbent efficiency is 77.00 % corresponding to adsorptive capacity 47.65 mg/g at room temperature. Keywords. Polyaniline, coir, DDT, adsorption, pesticide.